Tokopedia Marketplace, The Effect Of Digital Marketing And Service Quality On Purchase Decisions - Muhammad Yusuf; I Nyoman Tri Sutaguna; Mashudi Hariyanto; Rusydi Fauzan; Rahmadtiyah Hasanah Miftahuljannah (STIE AMKOP, 2023)
Traditional media marketing is becoming increasingly impacted by technology. Businesses can communicate, share information, and advertise their goods and services online. One of the online buying sites is Tokopedia. In Q1 2013, the top three online shopping platforms with the greatest growth in demand were Tokopedia, Amazon, and eBay. While Lazada and Shoppe, the two most popular online markets that are often downloaded on smartphones, have been the kings of online marketplaces, Tokopedia is the most commonly used application among Indonesians. This proves that Indonesians visit Tokopedia frequently and shop there right now. The purpose of this study is to ascertain (1) how digital marketing influences consumers' purchase choices on the Tokopedia marketplace. Kata Kunci: Word of Mouth , Digital Marketing, Service Quality, Decisions Purchase Tokopedia